Inhibition of PCAF by Anacardic Acid Derivative Leads to Apoptosis and Breaks Resistance to DNA Damage in BCR-ABL-expressing Cells - Kusio-Kobialka, Monika; Dudka-Ruszkowska, Wioleta; Ghizzoni, Massimo; Dekker, Frank J.; Piwocka, Katarzyna (Anti-Cancer Agents in Medicinal Chemistry, 2013)
Acetylation of histones and nonhistone proteins is a posttranslational modification which plays a major role in the regulation of intracellular processes involved in tumorigenesis. It was shown that different acetylation of proteins correlates with development of leukemia. It is proposed that histone acetyltransferases (HATs) are important novel drug targets for leukemia treatment, however data are still not consistent. Our previous data showed that a derivative of anacardic acid - small molecule MG153, which has been designed and synthesized to optimize the HAT inhibitory potency of anacardic acid, is a potent inhibitor of p300/CBP associated factor (PCAF) acetyltransferase. Here we ask whether inhibition of PCAF acetyltransferase with MG153 will show proapoptotic effects in cells expressing BCR-ABL, which show increased PCAF expression and are resistant to apoptosis. We found that inhibition of PCAF decreases proliferation and induces apoptosis, which correlates with loss of the mitochondrial membrane potential and DNA fragmentation. Importantly, cells expressing BCR-ABL are more sensitive to PCAF inhibition compared to parental cells without BCRABL. Moreover, inhibition of PCAF in BCR-ABL-expressing cells breaks their resistance to DNA damage-induced cell death. These findings provide direct evidence that targeting the PCAF alone or in combination with DNA-damaging drugs shows cytotoxic effects and should be considered as a prospective therapeutic strategy in chronic myeloid leukemia cells. Moreover, we propose that anacardic acid derivative MG153 is a valuable agent and further studies validating its therapeutic relevance should be performed.
Keywords: p300/CBP associated factor (PCAF)